Effects of driving styles on vehicle performance, fuel consumption and engine emissions - Hamed, Ali Mahmoud; Tuan Kamaruddin, Tengku Nordayana Akma (Universiti Teknikal Malaysia Melaka (UTeM), 2026)
Fuel consumption and emission rates are often determined under standardized laboratory test conditions to ensure comparability between vehicles. While these tests provide a useful benchmark, they do not fully reflect the complexities of actual driving environments. In real-world operation, vehicles are exposed to a wide range of conditions that differ significantly from those in controlled testing. As a result, there is a gap between real-world fuel consumption and the reported fuel consumption and emission rates. This paper studied the effect of driving styles including aggressive driving, unnecessary idling, and vehicle operating mass on vehicle performance, fuel consumption and emission rates for light duty vehicles. In order to investigate the effect of these different driving styles on the vehicle performance in a quantitative way, a detailed dataset and real-time measurement including instantaneous speed, acceleration, fuel consumption, oxygen content of the intake air, intake air temperature, and engine emission rates have been collected while driving a vehicle instrumented with vehicle data logger and on-board diagnostic scanner. The results showed that aggressive driving reduced the fuel efficiency by approximately 19% and consequently increased CO2 emissions by 40%. Vehicle operating mass increased CO2 emissions by 20% for an additional 100 kg. Idling condition produced hazardous emissions especially while warming up the engine. The findings highlight how informed driving habits can significantly contribute to reducing fuel consumption and lowering emissions